Grover's Disease after Heart Transplantation: A Case Report - Giovanbattista Ippoliti; Marco Paulli; Marco Lucioni; Andrea Maria D'Armini; Marinella Lauriola; Rany Mahrous Haleem Saaleb (Case Reports in Transplantation)
Grover's disease is a transient acantholytic dermatosis of unknown cause, manifesting clinically as a papular skin eruption that is usually located on the anterior chest and abdomen. Histologically characterized by an acantholytic pattern, it has been associated with numerous disorders, including hematologic malignancies, chronic renal failure, and HIV infection, as well as with chemotherapy and bone marrow and/or kidney transplant. Evaluation of followup and treatment is often complicated by spontaneous remission and the occasionally fluctuant course of the disease. Here we report the case of a patient with sudden onset of Grover's disease after heart transplantation. To the best of our knowledge, this is the first observation of Grover's disease as diagnosed after heart transplantation.